CcpA- and Shm2-Pulsed Myeloid Dendritic Cells Induce T-Cell Activation and Enhance the Neutrophilic Oxidative Burst Response to Aspergillus fumigatus - Page, Lukas; Wallstabe, Julia; Lother, Jasmin; Bauser, Maximilian; Kniemeyer, Olaf; Strobel, Lea; Voltersen, Vera; Teutschbein, Janka; Hortschansky, Peter; Morton, Charles Oliver; Brakhage, Axel A.; Topp, Max; et al. (Frontiers in Immunology, 2021)
Aspergillus fumigatus causes life-threatening opportunistic infections in immunocompromised patients. As therapeutic outcomes of invasive aspergillosis (IA) are often unsatisfactory, the development of targeted immunotherapy remains an important pursuit. Linking the innate and adaptive immune system, dendritic cells are pivotal in anti-Aspergillus defense and have gained interest as a potential immunotherapeutic approach in IA. While monocyte-derived dendritic cells (moDCs) require ex vivo differentiation, antigen-pulsed primary myeloid dendritic cells (mDCs) could present a more rapidly available platform for immunotherapy. To that end, we compared the response patterns and cellular interactions of human primary mDCs and moDCs pulsed with an A. fumigatus lysate and two A. fumigatus proteins (CcpA and Shm2) in a serum-free, GMP-compliant medium. CcpA and Shm2 triggered significant upregulation of maturation markers in mDCs and, to a lesser extent, moDCs. Furthermore, both A. fumigatus proteins elicited the release of an array of key pro-inflammatory cytokines including TNF-α, IL-6, IL-8, and CCL3 from both DC populations. Compared to moDCs, CcpA- and Shm2-pulsed mDCs exhibited greater expression of MHC class II antigens and stimulated stronger proliferation and IFN-γ secretion from autologous CD4+ and CD8+ T-cells. Moreover, supernatants of CcpA- and Shm2-pulsed mDCs significantly enhanced the A. fumigatus-induced oxidative burst of allogeneic neutrophils. Taken together, our in vitro data suggest that ex vivo CcpA- and Shm2-pulsed primary mDCs offer promising potential for the development of immunotherapeutic approaches to tackle IA.